Enhanced SLM based OFDM-DCSK communication system for PAPR reduction - Sajjad R. Abdulridha; Fadhil S. Hasan (Bulletin of Electrical Engineering and Informatics, 2022)
In this research, a selective mapping (SLM) technique using the Walsh Hadamard (WH) matrix, the Riemann matrix, and the new enhanced Riemann matrix were introduced to reduce the peak to average power ratio (PAPR) of orthogonal frequency division multiplexing based differential chaos shift keying (OFDM-DCSK). Using a new algorithm to reduce the size of the Riemann matrix, which in turn enhances the computational complexity of the SLM system without affecting the performance of PAPR in the main method. The simulation results show that the SLM technique using the Riemann matrix gives better PAPR performance than WH and conventional techniques by gaining about (6.3, 6.15) dB, respectively, for complementary cumulative distribution function (CCDF)=10-3 and the number of candidates U=16. Also, the results show that the SLM technique based enhanced Riemann matrix gives a reduction in computational complexity by reducing the number of candidates U to 4, while maintaining the same PAPR performance.